2012
DOI: 10.1016/j.str.2012.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Blind Testing of Routine, Fully Automated Determination of Protein Structures from NMR Data

Abstract: SUMMARY The protocols currently used for protein structure determination by NMR depend on the determination of a large number of upper distance limits for proton-proton pairs. Typically, this task is performed manually by an experienced researcher rather than automatically by using a specific computer program. To assess whether it is indeed possible to generate in a fully automated manner NMR structures adequate for deposition in the Protein Data Bank, we gathered ten experimental datasets with unassigned NOES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
77
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 53 publications
6
77
0
Order By: Relevance
“…However, a high deuteration level severely limits observation of side-chain signals, which are essential for the determination of a protein structure at high resolution. The redundancy of information intrinsic to spectra of side-chain protonated proteins, which leads to a mutually supportive network of distance restraints, is also crucial to an unbiased and robust spectral analysis by unsupervised algorithms (33)(34)(35)(36).…”
mentioning
confidence: 99%
“…However, a high deuteration level severely limits observation of side-chain signals, which are essential for the determination of a protein structure at high resolution. The redundancy of information intrinsic to spectra of side-chain protonated proteins, which leads to a mutually supportive network of distance restraints, is also crucial to an unbiased and robust spectral analysis by unsupervised algorithms (33)(34)(35)(36).…”
mentioning
confidence: 99%
“…This information has been used to characterize protein secondary structures (17,18) and to determine the allowed ranges of dihedral angles (19). More recently it has been demonstrated that by encoding the chemical shift information into molecular fragments it is possible to accurately determine the structures of smallto medium-sized globular proteins (14)(15)(16)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…A further problem is that the discrete fragment libraries may not necessarily cover the entire relevant space of protein conformations. Although fragment replacement methods are thus efficient in finding a structure compatible with the available data, it is not straightforward to demonstrate that such a structure actually represents the native state, even if, for practical purposes, it does so in most cases (22). Likewise, it is difficult to use fragment-based approaches to generate alternative conformers that represent the less densely populated regions of the native free energy landscape.…”
mentioning
confidence: 99%
“…Despite this, the use of chemical shifts for determination and refinement of protein structures (14)(15)(16)(17) is not the aim of this work, although a simple refinement routine is used here only as a tool to assess the reliability of a proposed methodology to repair flaws in proteins.…”
mentioning
confidence: 99%